Fabrication and Characterization of Multiferroic Al0.5Fe1.5O3 Epitaxial Thin Films. (19th February 2019) - Aroor Rao, Badari Narayana; Yasui, Shintaro; Katayama, Tsukasa; Itoh, Mitsuru
ABSTRACT: Single-phase multiferroic materials have attracted considerable attention among scientists, due to the strong drive in industry towards device miniaturization, addition of new functionalities, etc. Currently, most of the discovered materials have at-least one ferroic order active only at low temperatures, thereby hindering their induction into practical devices. κ-Al2 O3 -type Alx Fe2-x O3 (x-AFO) oxides belong to a new class of metastable multiferroic compounds (space group: Pna21 ), with relatively high Curie temperatures. The current work investigates the effect of thin film deposition conditions on the ferroelectric and ferrimagnetic properties of Al0.5 Fe1.5 O3 (0.5-AFO). Substrate temperature and oxygen partial pressure during deposition were found to be the critical parameters in obtaining high quality films. Optimizing the deposition conditions of 0.5-AFO enabled observation of both ferroelectricity and ferrimagnetism at room temperature.